How to p(l)ay with words? - Lazović, Vesna (ELOPE (Ljubljana), 2018)
Based on a corpus comprising online advertisements of banks operating in the UK and Serbia, this paper aims at describing the most frequent ways of creating puns and classifying them based on their predominant structure. The function of puns in advertising is explained from the perspective of Sperber and Wilson's relevance theory (1995) and the behavioural AIDA model. This paper also tries to reveal whether the formal and semantic aspects of lexical units are exploited in British and Serbian bank offers, and whether there are any language- and culture-specific features in terms of punning.
Keywords: angleščina; bančni oglasi; besedne igre; srbščina; teorija relevantnosti